Establishing a Model Cancer Registry in Senegal: A Blueprint for Developing Nations - Baldé, Salif; Niang, Sokhna Diop; Oumar Ba; Diop, Mamadou (Medical Research and Its Applications Vol. 4, 2024)
Background and Objectives: Senegal, with the support of WHO, had begun the establishment of a National Cancer Registry in 2009, although it had been at a standstill since 1969; the objective of this work was to test the reliability of data collection tools and feasibility stages necessary for the validation of media before the establishment of a national cancer registry. Methodology: We conducted a non-exhaustive preliminary study over a period of three months from the first of January to 31 March 2010 at four major hospitals in Dakar at the time. Patients’ records were used as our source of information, data collection was done using a pre-established patient form, and data processing and validation were done using Wed-Dev software. Results: Two hundred and eighty-nine cases had been identified: 44% of men (n = 127) and 56% of women (n = 162) with a sex ratio of 0.8. The ages ranged from 20 to 90 years with an average of 50 years. The main diagnostic mode was essentially histological, with 76% of cases (n = 219). The most frequent locations were: ORL (ENT meaning Ear, Nose and Throat) with 25% of cases, liver 7% and bronchopulmonary with 4.5% of cases. In men, liver cancer was the most common location and in women for cervical cancer with 16%. Squamous cell carcinoma was the most common histological type with 68% of cases followed by adenocarcinoma with 22% of cases. Thirty-eight percent of patients were classified as stage III and IV. A quarter of our patients had received palliative treatment. In contrast, 15 (15%) had received chemotherapy and 4% had received radiotherapy. Data collection was satisfactory. Conclusion: Cancer is a reality in Senegal but it remains underdiagnosed. The materials made it possible to make the cancer registry effective throughout the country. The recommendations enabled the extension of registration in hospitals throughout the country and started an effective cancer registry in Senegal.